DESIGN OF GEOTHERMAL POWER PLANT UTILIZING EXCEES STEAM CASE STUDY PT INDONESIA POWER UBP KAMOJANG - MOCHAMAD IQBAL (NIM : 131 06 114); Pembimbing : Prof. Dr. Ir. T.A. Fauzi Soelaiman, MSME, RIZA
Geothermal energy development can be done not only using existing geothermal wells but also optimizing existing geothermal power plants. Geothermal power plants existing in Kamojang among others are units 1, 2, and 3 owned by PT Indonesia Power. Nowadays, it is calculated that there is excess hot steam of 28,45 kg/s discharged at vent structure as part of agreement between PT Pertamina Geothermal Energy and PT Indonesia Power as compensation from losses on steam transportation. In this final project, an addition geothermal power plant is designed using a direct dry steam cycle and utilizing the excess steam. The design was performed by modeling the power plant and optimizing it by varying condenser pressure and gas removal system configurations for generating optimum turbine power output. The calculations show that the optimum turbine power output is 15.19 MW, with turbine power and auxiliary power are 15.94 MW and 755.18 kW respectively. This condition can be obtained using 6.5 bar inlet turbine pressure, 0.07 bar condensor presssure, and one stage liquid ring vacuum pump (LRVP) gas removal system. Auxiliary power is used for operating pump, cooling tower fan, LRVP, and other components. In this final project sizing of separator and demister were also performed.